THE INFLUENCE OF PERSUASIVE COMMUNICATION ON THE INSTAGRAM ACCOUNT OF MOP (MOTHER OF PEARL) BEAUTY ON CONSUMER BUYING INTEREST - Devi Amelia Putri; Danang Trijayanto (RADJA PUBLIKA, 2025)
This study aims to measure the influence of persuasive communication by influencers on @mop.beauty's Instagram account on consumer buying interest. In the digital era, social media has become the main tool in marketing beauty products. The study used a quantitative approach with an online survey method to 100 respondents who were followers of the account. The Elaboration Likelihood Model (ELM) theory is used to analyze the persuasion process through central and peripheral pathways. The results of the study showed that persuasive communication had a positive and significant influence on consumer buying interest, with a contribution of 64.8%. The most influential factors include the communicator's credibility, emotional appeal, and delivery style in visual content. These findings confirm the importance of effective communication strategies in shaping purchase intentions on social media.